A Sociological Study on Role and Challenges of Agrarian Communities in Contemporary Rural Societies - Samarakoon, MT (My University, 2019)
Agriculture constitutes one of the key industries in the national economy in Sri Lanka similar to many other countries those are in the process of development. Nevertheless, It is noticeable that the effects of modernization of traditional peasantry communities and the changes happened therein had caused certain drawbacks on Agriculture. In this regard, the purpose of this Research was to appraise the role of traditional farmers in the contemporary agricultural social system and to assert the challenges being faced by them. In so doing this study was focused on 6 Grama Niladhari divisions namely; Suhadagama, Kumarigama, Gonagama, Galapitagala, Rajagama and Senagama in the Uhana DS’s area in the Ampara district in Sri Lanka in line with a random sampling method having selected 870 for the sample. It was revealed that the category of youth nowadays, have shown fairly minimal attention on Agro-based activities. Moreover, one other set back is the marginal contribution of Government for those involved in Agriculture. In overall context, the concluding remarks of the Research is that a division of farmers faces problems due to the unavailability of quality seeds, and fertilizer, the majority of them not facing solemn problems. Also the outcomes of this research might be important in policy making for the Agricultural sector by required .bodies of Government
Keywords: Agriculture, farmers’ Role, Modernization, Rural Community